THE INFLUENCE OF USING COMICS STRIPS IN TELLING STORIES AND STUDENTS’ LEARNING MOTIVATION TOWARD THE READING ABILITY OF THE EIGHTH GRADE STUDENTS AT SMPI MARYAM MURAIT MARTAPURA - Murti Sari Dewi (Universitas PGRI Palembang, 2022)
The objective of this study is to find out whether or not there is any significant effect on the eight grade students’ learning motivation toward the reading ability after being taught by using comics strips. The population of this study was the eight grade students at SMPI Maryam MuraitMartapura in academic 2021/2022. The total number of the population was 142 students, The sample was consisted of 36 students of R1 and 36 students of R2. The method of the study was the experimental method and the data were collected through written test in multiple choice form. The test was administrated twice as the pre-test and post-test. The result were analyzed by using t-test. The students’ Mean score of pretest and post-test in control class of R1 were 46.11 and 6,67. While the students’ Mean score of Pretest and post test in experimental class of R2 were 46,67 and 5,56. The null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.